The Relationship Between Marketing Strategies and Customer Satisfaction in the Fast-Food Restaurant Industry - Santos, John Angelo; Sotelo-Drequito, Glory (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
This research examines the relationship between marketing strategies and customer satisfaction within the fast-food restaurant industry, focusing on product and promotional strategies. The study unveils critical insights gathered from a representative sample of 400 respondents. Findings reveal that product strategies, such as incorporating local and international flavors, offering unique menu items, introducing new products, and improving existing offerings, significantly attract and satisfy customers. Moreover, emotionally resonant promotional strategy and celebrity endorsements have a compelling impact on customer purchasing decisions. The study underscores the importance of a comprehensive marketing approach, harmonizing both product and promotional strategies, in enhancing overall customer satisfaction. The positive correlations observed between marketing strategies and customer satisfaction highlight the paramount role of marketing strategies in shaping the success of fast-food restaurants, underscoring their crucial influence on customer satisfaction and overall restaurant performance. These findings provide actionable recommendations for the industry, emphasizing the need for adaptability, convincing advertisements, and culinary innovation to meet evolving consumer preferences and expectations.